Optimization of Oxygen Flow Valve Holes in Small Industrial Scale Husk Furnaces - Hajar, Siti; Har, Nazopatul Patonah; Irmansyah, Irmansyah; Arif, Ardian; Irzaman, Irzaman (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
The increasing use of fossil-based fuels causes an imbalance between energy demand and the availability of that energy. Therefore, the use of rice husk biomass as alternative energy was implemented through the use of rice husk furnaces. This research aims to optimize the efficiency of a small industrial-scale husk furnace by varying the oxygen flow valve holes and the mass of the heated water. The test on the husk furnace was carried out using the Water Boiling Test (WBT) method with the following test parameters: combustion time, FCR, input power, output power, power loss, radiant energy, and thermal conductivity of the pan and chimney of the husk furnace. Tests were carried out on four variations of the oxygen flow valve holes (horizontal: 18 x 36 cm2 and 27 x 36 cm2, vertical: 27 x 24 cm2 and 27 x 12 cm2) and three variations in the mass of heated water (6 kg, 12 kg, and 18 kg). The highest efficiency of the husk furnace was obtained at 18 kg of water, and based on each test parameter, the performance of the husk furnace was most optimal at the horizontal valve hole measuring 27 x 36 cm2 with an average efficiency of 17.32%.